Assessment of shock pretreatment and alkali pretreatment on corn stover using enzymatic hydrolysis - Olokede, Opeyemi; Hsu, Shen‐chun; Schiele, Simon; Ju, Huang; Holtzapple, Mark (Biotechnology progress, 2022)
This study investigates digestibility enhancements of lignocellulose from shock pretreatment, alkaline pretreatment, and combination. Shock pretreatment subjects aqueous slurries of lignocellulose to shock waves, which disrupts its structure rendering it more susceptible to hydrolysis. Alkaline pretreatment submerges the biomass in aqueous alkali (NaOH, Ca(OH)2), which removes lignin and acetyl groups. As indicators of digestibility, cellulase (CTec3) and hemicellulase (HTec3) were used to saccharify the pretreated corn stover and the resulting filtrate which contains about 10% of the sugars. Shock is most effective when it precedes alkaline pretreatment, presumably because it opens the biomass structure and enhances diffusion of pretreatment chemicals. Lignocellulose digestibility from calcium hydroxide treatment improves significantly with oxygen addition. In contrast, sodium hydroxide is a more potent alkali, and thereby eliminates the need for oxygen to enhance pretreatment. At low hydroxide loadings (<4 g OH−/100 g dry biomass), both NaOH and Ca(OH)2 provide similar increases in digestibility; however, at high hydroxide loadings, NaOH is superior. For animal feed, Ca(OH)2 treatment is recommended, because residual calcium ions are valuable nutrients. In contrast, for methane‐arrested anaerobic digestion, NaOH treatment is preferred because NaHCO3 is a stronger buffer. At 50°C, shock pretreatment improves sugar yields at all NaOH loadings. The effect of shock is most pronounced when the no‐shock control employed the same soaking‐and‐drying procedure as the shock treatment. The recommended conditions are shock treatment (5.52 bar [abs] initial H2/O2 pressure) followed by 50°C alkaline treatment with NaOH loading of 4 g OH−/100 g dry biomass for 1 h.